PELATIHAN PEMBUATAN BATIK REMUKAN BAGI SISWA SMK DIPONEGORO DEPOK SLEMAN - Sugiyem, Sugiyem; Widarwati, Sri; Budiastuti, Emy (Prosiding Pendidikan Teknik Boga Busana, 2020)
The purpose of this training activity is to provide knowledge and skills to make batik remukan as a continuation of the process of making batik colet and batik jumputan. The target of the activity is class XI students of the Boutique Clothing Department at SMk Diponegoro Depok Sleman.The method used in this training activity was a lecture to convey the theory of batik remukan, demonstration of making batik remukan, and the practice of making batik scarf with crushing technique using paraffin. Participants practice nglowong, nerusi, applying paraffin, dyeing basic colors and removing batik candles. The color used is napthol with one dye. The results of the activity: (1) The implementation of practical activities to make a scarf with a crushing technique which was attended by 30 students. (2) The training of students in making scarft with the technique of batik crushing. Based on the evaluation of the process of attendance the participants during the training are 100% fulfilled. While based on the results of 52% student practice, the students tunnel in good categories while 48% are in the fairly good category. Based on the combination of klowongan and remukan 76% are in the good category, 24% in the sufficient category. In terms of neatness as much as 68% of students are in the good category while 32% are in the sufficient category Keywords: training, batik remukan